One-Year Quality of Life Trends in Early-Stage Lung Cancer Patients After Lobectomy - Marzorati, Chiara; Mazzocco, Ketti; Monzani, Dario; Pavan, Francesca; Casiraghi, Monica; Spaggiari, Lorenzo; Monturano, Massimo; Pravettoni, Gabriella (Frontiers in Psychology, 2020)
Objective Quality of Life (QoL) is an important predictor of patient’s recovery and survival in lung cancer patients. The aim of the study is to identify one-year trends of lung cancer patients’ QoL after robot-assisted or traditional lobectomy and investigate whether clinical (e.g. pre-surgery QoL, type of surgery, and perioperative complications) and sociodemographic variables (e.g. age) may predict these trends. Methods An Italian sample of 176 lung cancer patients undergoing lobectomy completed the EORTC QLQ-C30 at the pre-hospitalization (t0), 30 days (t1), 4 months (t2), 8 months (t3), and 12 months (t4) after surgery. Sociodemographic and clinical characteristics (age, gender, perioperative complications, and type of surgery) were also collected. The individual change over time of the fifteen dimensions of the EORTC QLQ-C30 and the effects of pre-surgery scores of QoL dimensions, type of surgery, perioperative complications, and age on patients’ QoL after surgery were studied with the individual growth curve (IGCs) models. Results Patients had a good recovery after lobectomy: functioning subscales improved over time, while most of the symptoms became less severe over the care process. Perioperative complications, type of surgery, pre-surgery status, and age significantly affected these trends, thus becoming predictors of patients’ QoL. Conclusion This study highlights different one-year trends of lung cancer patients’ QoL. The measurement of pre- and post-surgery QoL and its clinical and sociodemographic covariables would be necessary to better investigate patients’ care process and implement personalized medicine in lung cancer hospital divisions.